HIC1 (Hypermethylated in Cancer 1) modulates the contractile activity of prostate stromal fibroblasts and directly regulates CXCL12 expression - Dubuissez, Marion (Impact Journals LLC, 2020)

(untitled) (Oncotarget)
HIC1 (Hypermethylated In Cancer 1) a tumor suppressor gene located at 17p13.3, is frequently deleted or epigenetically silenced in many human tumors. HIC1 encodes a transcriptional repressor involved in various aspects of the DNA damage response and in complex regulatory loops with P53 and SIRT1. HIC1 expression in normal prostate tissues has not yet been investigated in detail. Here, we demonstrated by immunohistochemistry that detectable HIC1 expression is restricted to the stroma of both normal and tumor prostate tissues. By RT-qPCR, we showed that HIC1 is poorly expressed in all tested prostate epithelial lineage cell types: primary (PrEC), immortalized (RWPE1) or transformed androgen-dependent (LnCAP) or androgen-independent (PC3 and DU145) prostate epithelial cells. By contrast, HIC1 is strongly expressed in primary PrSMC and immortalized (WMPY-1) prostate myofibroblastic cells. HIC1 depletion in WPMY-1 cells induced decreases in α-SMA expression and contractile capability. In addition to SLUG, we identified stromal cell-derived factor 1/C-X-C motif chemokine 12 (SDF1/CXCL12) as a new HIC1 direct target-gene. Thus, our results identify HIC1 as a tumor suppressor gene which is poorly expressed in the epithelial cells targeted by the tumorigenic process. HIC1 is expressed in stromal myofibroblasts and regulates CXCL12/SDF1 expression, thereby highlighting a complex interplay mediating the tumor promoting activity of the tumor microenvironment. Our studies provide new insights into the role of HIC1 in normal prostatic epithelial-stromal interactions through direct repression of CXCL12 and new mechanistic clues on how its loss of function through promoter hypermethylation during aging could contribute to prostatic tumors.